Transmedia Narratives for the Communication of Cultural Heritage and Memory of the City of São Bernardo do Campo in ABC Paulista (Intercom - Brazilian Journal of Communication Sciences, 2025)
Cultural heritage is a relevant contemporary theme and must be rethought in a more inclusive way, to give visibility to new narratives evidenced by the memories of the inhabitants of the city of São Bernardo do Campo, and to assume contemporary narrative forms to value the communication of public interest of the heritage with their own local community. With a qualitative, documentary approach, and a theoretical-methodological framework aligned with Cultural Studies, this work seeks to point out the possibilities of transmedia communication in the dissemination of cultural heritage, formulated through the oral and photographic narratives of residents of the City. The research results enabled the development of the transmedia product Caçadores de Histórias do ABC and indicate the innovative potential of oral and photographic narratives for communication studies of public interest for the appreciation of the heritage, memory and culture of the cities.
Keywords: cultural heritage; social memory; public interest; transmedia storytelling; city